'Green' fluorine-free mesoporous iron(III) trimesate nanoparticles for drug delivery. Issue 4 (1st December 2013) - Willaime, Hervé; Gref, Ruxandra; Horcajada, Patricia; Couvreur, Patrick; Rodriguez-Ruiz, Violeta; Agostoni, Valentina; Serre, Christian
Abstract : A comparison of the properties of the highly porous iron(III) trimesate MIL-100 nanoparticles (nano-MOFs) obtained through a hydrofluoric acid-free 'green' synthesis route with those obtained from the 'conventional' HF procedure is reported, in terms of particle crystallinity, porosity and space time yield (STY). It appears that the use of more concentrated reaction conditions have led to the highest STY values while maintaining a good degree of purity. As the fluorinated nano-MOFs, the F-free solids are able to encapsulate high payloads of a challenging antiviral drug, azidothymidine triphosphate, and to release it on a progressive manner. Furthermore, the F-free nano-MOFs were shown to be highly taken up by macrophages, targets for antiviral therapy, without inducing any detectable toxic side effects. This study opens up novel perspectives for the large-scale synthesis of 'green' MIL-100 nano-MOFs for biomedical applications. Supplementary information will be available at http://www.icevirtuallibrary.com/upload/10.1680gmat.13.00001_SupplementaryInformation.pdf